IMPLEMENTASI IME (ILEARNING MEDIA)DALAM MENDUKUNG SISTEM PEMBELAJARAN ILEARNING PADA PERGURUAN TINGGI - Untung Rahardja; Sudaryono Sudaryono; Irwan Nurdin (CCIT Journal, 2014)
The learning system is run in an educational institution, strongly influence the mindset and creativity of each student. In a learning system running on colleges Raharja, currently still using paper as a medium for performing tasks. The use of paper is a way of learning the manual and monotonous. To support that learning systems can be more interesting is to utilize existing information technology. iLearning is a method of lecturing in colleges Raharja who use the iPad as a media to facilitate the learning process of students. Given this method, students can learn, work, pray and play with iPad. The term is known as 4B. iLearning Media or shortened by the name iMe is a web application that is created and can be used by all students of colleges Raharja to explore their creativity in learning. This is an online learning system that facilitates student learning, because it can be done anywhere and anytime. It was concluded that the contribution of the iMe can be used as a medium of information for learning systems for the entire community colleges Raharja. Research methods used in conducting this research is the method of observation and literature